2020
DOI: 10.1186/s12981-020-00311-1
|View full text |Cite
|
Sign up to set email alerts
|

Level of knowledge, acceptability, and willingness to use oral fluid HIV self-testing among medical students in Kilimanjaro region, Tanzania: a descriptive cross-sectional study

Abstract: Background HIV Self-Testing (HIVST) is universally accepted as an innovative strategy complimenting existing HIV testing services to archive the UNAIDS, 95-95-95 goals by 2030. However, the adoption of HIVST is lagging in most sub-Saharan countries, including Tanzania. This study aimed to determine the level of knowledge, acceptability, and willingness to use HIVST among Medical students in Kilimanjaro region, Tanzania. Methods A descriptive cross-sectional study using a self-administered, semi-structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 58 publications
4
16
1
Order By: Relevance
“…This is similar to the average age found in a study done among medical students in the Kilimanjaro region in Tanzania. This Tanzanian study revealed that the average age for sexual debut was 19 (Vara et al, 2020) and the majority of respondents (73.2%) reported using a condom on the first sexual encounter which corroborates with a study by Dzinamarira and colleagues showing 75 % of the participants using a condom on their first sexual encounter (Dzinamarira et al, 2020). Consistency of condom use is confirmed by 49.5% of the respondents, while 7.2% reported that they never use condoms during sex.…”
Section: Sexual Health and Health Seeking Behaviour Characteristicssupporting
confidence: 87%
“…This is similar to the average age found in a study done among medical students in the Kilimanjaro region in Tanzania. This Tanzanian study revealed that the average age for sexual debut was 19 (Vara et al, 2020) and the majority of respondents (73.2%) reported using a condom on the first sexual encounter which corroborates with a study by Dzinamarira and colleagues showing 75 % of the participants using a condom on their first sexual encounter (Dzinamarira et al, 2020). Consistency of condom use is confirmed by 49.5% of the respondents, while 7.2% reported that they never use condoms during sex.…”
Section: Sexual Health and Health Seeking Behaviour Characteristicssupporting
confidence: 87%
“…From this study, KPs can strongly network to increase awareness and access to PrEP and HIVST services in Nigeria, as applied to other settings [20][21]. This is quite encouraging considering the importance of peer in uence in producing multiplier effects in behaviours.…”
Section: Discussionmentioning
confidence: 58%
“…Cross-cutting factors that may encourage an implementation of sustainable and targeted strategies that are KP-friendly to acquiring PrEP and HIVST messages were elicited from the study. The ndings suggest that dissemination of PrEP and HIVST messages will require the use a targeted messaging and disaggregated audience, hence, content should consider the preferences of the KP groups for effective and sustainable impacts [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that the dissemination of PrEP and HIVST messages will require a targeted and disaggregated audience. Hence, content should consider the preferences of the KP groups for effective and sustainable impacts [ 20 , 21 ]. Emphasis should be on the specific channels that best attract the attention of the KP groups in dispelling misconceptions, stigma, discrimination, fears, and other barriers that may be contextual to increase the acquisition and use of PrEP and HIVST messages.…”
Section: Discussionmentioning
confidence: 99%
“…From this study, KPs can effectively network to increase awareness and access to PrEP and HIVST services in Nigeria, as applied to other settings [ 20 , 21 ]. That is quite encouraging considering the importance of peer influence in producing multiplier effects in behaviours.…”
Section: Discussionmentioning
confidence: 99%